Inhibition of UDP‐glucosylceramide synthase in mice prevents Gaucher disease‐associated B‐cell malignancy. Issue 1 (January 2015) - Pavlova, Elena V; Archer, Joy; Z Wang, Susan; Dekker, Nick; Aerts, Johannes MFG; Karlsson, Stefan; Cox, Timothy M
Abstract Clonal B‐cell proliferation is a frequent manifestation of Gaucher disease – a sphingolipidosis associated with a high risk of multiple myeloma and non‐Hodgkin lymphoma. Gaucher disease is caused by genetic deficiency of acid β‐glucosidase, the natural substrates of which (β‐d‐glucosylceramide and β‐d‐glucosylsphingosine) accumulate, principally in macrophages. Mice with inducible deficiency of β‐glucosidase [Gba(tm1Karl/tm1Karl)Tg(MX1‐cre)1Cgn/0] serve as an authentic model of human Gaucher disease; we have recently reported clonal B‐cell proliferation accompanied by monoclonal serum paraproteins and cognate tumours in these animals. To explore the relationship between B‐cell malignancy and the biochemical defect, we treated Gaucher mice with eliglustat tartrate (GENZ 112638), a potent and selective inhibitor of the first committed step in glycosphingolipid biosynthesis. Twenty‐two Gaucher mice received 300 mg/kg of GENZ 112638 daily for 3–10 months from 6 weeks of age. Plasma concentrations of β‐d‐glucosylceramide and the unacylated glycosphingolipid, β‐d‐glucosylsphingosine, declined. After administration of GENZ 112638 to Gaucher mice for 3–10 months, serum paraproteins were not detected and there was a striking reduction in the malignant lymphoproliferation: neither lymphomas nor plasmacytomas were found in animals that had received the investigational agent. In contrast, 14 out of 60 Gaucher mice without GENZ 112638 treatment developed these tumours; monoclonal paraproteins were detected in plasma from 18 of the 44 age‐matched mice with Gaucher disease that had not received GENZ 112638. Long‐term inhibition of glycosphingolipid biosynthesis suppresses the development of spontaneous B‐cell lymphoma and myeloma in Gaucher mice. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.